IMPROVING THE PROCESS AND RESULTS OF MATHEMATICAL LEARNING USING THREE DIMENSIONAL LEARNING MEDIA IN BEAM AND CUBE SPACE MATERIALS THROUGH STADD TYPE COOPERATIVE LEARNING MODEL - Nolit Triyanto; Raafi Fauzia Hakim; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2018)
The background of this research is that in the field there are still many teachers who do not pay attention to the potential of students to develop social skills and learning outcomes. STAD type cooperative learning model is one small group learning model between 4-5 people with different backgrounds to complete a task for a common goal. This model can also foster positive social skills for students. The most visible stages of growing social skills are discussion and evaluation. The research method used is classroom action research. This research is designed with a cycle model that is repeatable and sustainable. The research subjects were students in grade IV of Public Elementary School 031 Pelesiran with a total of 28 people. Research instruments are student worksheets (LKS), process assessment sheets, test questions, observation sheets, documentation. The results showed that there was an increase in the results of mathematics learning material in building the beam and cube space of the fourth grade students with STAD type Cooperative Learning models using three-dimensional media in the form of models of space building. The results showed that the STAD type Cooperative Learning model using three-dimensional media can improve student learning processes and results in learning to build a beam space and cube.